2022
DOI: 10.1186/s12889-022-13236-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 vaccine acceptability among health professions students in Vietnam

Abstract: Background The COVID-19 vaccine hesitancy or refusal has actually been a threat to global health. In the current situation, health professions students are at risk for SARS-CoV-2 infection during their internship at healthcare facilities. Furthermore, those future healthcare workers will advise people to accept the COVID-19 vaccination. Therefore, the attitude of students towards vaccine acceptance and the predicting factors needs to be elucidated. This study applied the Health Belief Model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
2
7
1
Order By: Relevance
“…Vietnam succeeded in risk communication regarding COVID-19 with diversified communication of information through various channels, including television, online newspapers, social media and broadcasts. 24 We found that most respondents would get vaccinated if they were recommended by a health worker, which is similar to UNICEF’s findings that health workers were rated as the most trusted source of information. 50 Individuals with better information access (6–16 channels and daily) were more likely to accept all types of available vaccines.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Vietnam succeeded in risk communication regarding COVID-19 with diversified communication of information through various channels, including television, online newspapers, social media and broadcasts. 24 We found that most respondents would get vaccinated if they were recommended by a health worker, which is similar to UNICEF’s findings that health workers were rated as the most trusted source of information. 50 Individuals with better information access (6–16 channels and daily) were more likely to accept all types of available vaccines.…”
Section: Discussionsupporting
confidence: 86%
“…Deployment timing played an important role as for COVID-19 vaccines, the participants were more willing to be immunised if they felt they were being exposed to higher risk of infection and mortality. 24 25 Mass vaccination for adolescents and general populations occurred in July and November 2021 respectively, during the fourth wave when the highly infectious and lethal Delta variant spread throughout Vietnam. These circumstances could have contributed to higher vaccination uptake among the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most typical preventive behaviors such as planning to get vaccinated, accepting vaccinations, wearing a face mask, keeping social distance, washing hands with soap and water, using hand sanitizer, self-quarantining, staying at home, not touching one's face, and not going to public meetings. In this review, COVID-19 vaccine acceptance was positively correlated with all HBM constructs (perceived susceptibility, perceived severity, perceived barrier, perceived benefit, cues to action, and self-efficacy), 23,[28][29][30][31][32] and constructs were also correlated with behavioral intention to engage in COVID-19 preventive behavior. 24,[33][34][35][36][37] The application of TPB to COVID-19 preventive behaviors is based on 27 articles included in this systematic review, and the dimensions of TPB (attitude, social norm, and perceived behavioral control) were significantly associated with COVID-19 preventive behaviors.…”
Section: Application Of Behavioral Change Theory and Model On Covid-1...mentioning
confidence: 81%
“…Various models have been conceptualized to explain behavioral and physiological determinants of vaccine acceptance [ 19 , 20 , 21 ]. The 5C model of psychological antecedents to vaccination is a framework that was developed to explain the various factors that influence an individual’s decision to get vaccinated [ 22 ].…”
Section: Introductionmentioning
confidence: 99%